2021
DOI: 10.1016/j.accpm.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width and mortality of COVID-19 patients

Abstract: Highlights Non-surviving showed higher RDW than surviving patients There is an association between RDW and mortality RDW could be used as mortality biomarker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 37 publications
(55 reference statements)
3
58
1
1
Order By: Relevance
“…After a full-text review of the remaining 12 articles, one further study was excluded because of missing information. Thus, 11 studies were included in the meta-analysis [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Their characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After a full-text review of the remaining 12 articles, one further study was excluded because of missing information. Thus, 11 studies were included in the meta-analysis [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Their characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4901 COVID-19 patients were studied, 4247 (50% males, mean age 52 years) with low severity or who survived and 654 (57% males, mean age 66 years) with high severity or who died. Two studies were prospective [ 34 , 36 ], while the remaining nine were retrospective [ 30 , 31 , 32 , 33 , 35 , 37 , 38 , 39 , 40 ]. Six studies were performed in Asia [ 30 , 33 , 35 , 38 , 39 , 40 ], three in Europe [ 32 , 36 , 37 ], and two in America [ 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with pneumonia, specifically, RDW was associated with both short-and longterm mortality in multiple studies (12)(13)(14)(15). Recently RDW has also been suggested to be of prognostic value in patients with COVID-19 (16)(17)(18)(19)(20). Most notably, Foy et al found a significantly increased mortality risk in patients with elevated RDW at the time of hospital admission with a hazard ratio of 2.01 when using a cut-off of 14.5% (21).…”
Section: Introductionmentioning
confidence: 99%